Session III: Issues Concerning Enforcement and Dispute Resolution - Tepp, Steven (The Columbia Journal of Law & the Arts, 2017)
These remarks are a transcript of a talk that was given on October 14, 2016, at the Kernochan Center Annual Symposium at Columbia Law School. Session III addressed the strategies for achieving compliance with international copyright treaties and trade agreements. Session Panelists: Sean Flynn, Associate Director for Program on Information Justice and Intellectual Property, American University Washington College of Law Maria Strong, Deputy Director of Policy and International Affairs, U.S. Copyright Office Antony Taubman, Director of the Intellectual Property Division of the World Trade Organization Steven Tepp, President and Founder of Sentinel Worldwide